2007
DOI: 10.1038/sj.ejhg.5201774
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of reproductive decision-making in asymptomatic carriers of the Huntington mutation

Abstract: The aim of this study was to describe reproductive decisions in mutation carriers after predictive testing for Huntington's disease (HD) and to identify factors that play a role in decision-making. In -2004 individuals received a predictive test result; 89 of them were carriers and seven received an equivocal result. Quantitative data on reproductive behaviour have been collected during all follow-up contacts. The follow-up time in this study was 1-16 years (mean: 7.1 years). Qualitative data on reproductive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 32 publications
6
110
0
Order By: Relevance
“…This study added new findings of benefits, beyond family closeness (Vamos et al, 2007), from those who had not undergone testing at the time of enrollment in the parent study, but who had a family history of HD. Those who had completed genetic testing endorsed benefits previously reported, including relief from uncertainty of one's gene status, appreciation for the present, acquiring significant life knowledge, making future plans, and reproductive decisions (Bloch et al, 1992;Decruyenaere et al, 2004Decruyenaere et al, , 2007Taylor, 2004;Duncan et al, 2008). The benefits included topics that are similar to those reported from qualitative descriptive studies.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This study added new findings of benefits, beyond family closeness (Vamos et al, 2007), from those who had not undergone testing at the time of enrollment in the parent study, but who had a family history of HD. Those who had completed genetic testing endorsed benefits previously reported, including relief from uncertainty of one's gene status, appreciation for the present, acquiring significant life knowledge, making future plans, and reproductive decisions (Bloch et al, 1992;Decruyenaere et al, 2004Decruyenaere et al, , 2007Taylor, 2004;Duncan et al, 2008). The benefits included topics that are similar to those reported from qualitative descriptive studies.…”
Section: Discussionmentioning
confidence: 87%
“…This category pertains to planning that was important to the person and his/her family, and included reproduction, work or retirement, finances for family after the person has died, and planning on behalf of their children. This category may overlap with benefits previously reported that include reproductive decisions (Decruyenaere et al, 2007) as well as more general comments in the literature related to significant life knowledge. One example in this category was regarding reproduction: ''My husband and I decided not to have children'' (10GT,F).…”
Section: Williams Et Almentioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, closely related was the opinion that the most important advantage of genetic testing was prevention of occurrence by not having children. Such an opinion was also found among those affected by Huntington's disease (Decruyenaere et al 2007). …”
Section: Discussionmentioning
confidence: 58%
“…At first glance, our participants echoed those affected by Huntington's disease who appreciated genetic tests as a ground for their decisions about planning their future (Taylor 2004;Decruyenaere et al 2007). However, when asked for practical examples of planning for visual disability, our participants could recall only a very limited number of practical examples, and found such a notion "ridiculous".…”
Section: Discussionmentioning
confidence: 94%